Respuesta :

Simplifying

7(42x + -8) = 17(49 + x)

Reorder the terms:

7(-8 + 42x) = 17(49 + x)

(-8 * 7 + 42x * 7) = 17(49 + x)

(-56 + 294x) = 17(49 + x)

-56 + 294x = (49 * 17 + x * 17)

-56 + 294x = (833 + 17x)

Solving

-56 + 294x = 833 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.

-56 + 294x + -17x = 833 + 17x + -17x

Combine like terms: 294x + -17x = 277x

-56 + 277x = 833 + 17x + -17x

Combine like terms: 17x + -17x = 0

-56 + 277x = 833 + 0

-56 + 277x = 833

Add '56' to each side of the equation.

-56 + 56 + 277x = 833 + 56

Combine like terms: -56 + 56 = 0

0 + 277x = 833 + 56

277x = 833 + 56

Combine like terms: 833 + 56 = 889

277x = 889

Divide each side by '277'.

x = 3.209386282

Simplifying

x = 3.209386282